Building knowledge to improve access to inclusive and equitable care for trans and gender-diverse survivors of sexual assault and intimate partner violence: a qualitative research protocol - Alexa R Yakubovich; Janice Du Mont; Sarah Daisy Kosa; Sheila Macdonald; Danielle Toccalino; C Emma Kelly; Sav Jonsa; Adam Davies (BMJ Open)
Introduction Intimate partner violence (IPV) and sexual assault are pervasive public health and human rights concerns that disproportionately impact trans and gender-diverse (TGD) individuals. Experiences of cisgenderism and transphobia, compounded by racism and other forms of discrimination and structural violence, can hinder access to appropriate supports in a safe and non-stigmatising environment across a variety of sectors, including but not limited to healthcare, social services, criminal justice, and legal. TGD individuals may also have unique health and social needs requiring support that is not yet in place. Recent research has identified the need to better understand barriers to accessing support for TGD survivors of IPV and sexual assault as a top priority. This study aims to address this need for evidence to facilitate improved access to inclusive and equitable services for TGD survivors.Methods and analysis This qualitative study will involve semi-structured interviews with approximately 60 adult TGD survivors of IPV and/or sexual assault who wanted to access, attempted to access, or used services. A diverse array of participants from across Canada will be recruited via purposeful and snowball sampling through partner organisations, Peer Leader Advisors and their networks, as well as promotion in physical and virtual spaces (eg, flyers and social media). An interview guide was developed based on Levesque’s access to care model. Virtual interviews will be thematically analysed using Braun and Clarke’s iterative phases of reflexive thematic analysis. An intersectionality lens will be applied throughout the research process.Ethics and dissemination Research Ethics Board approval was obtained from Women’s College Hospital (WCH REB #: 2023-0033-E). Findings will be shared in peer-reviewed publications, at academic conferences, and through the burgeoning trans-LINK Canada Network WebPortal (https://www.translinknetwork.com/) using a variety of media, including newsletters, infographics, and webinars.